Long‐Term Outcome and Quality of Life in Patients With Stroke Presenting With Extensive Early Infarction - Morin Beyeler; Loris Weber; Eric Buffle; Christoph C. Kurmann; Eike Immo Piechowiak; Mattia Branca; Thomas Raphael Meinel; Simon Jung; David Seiffge; Mirjam R. Heldner; Sara M. Pilgram‐Pastor; Tomas Dobrocky; et al. (Stroke: Vascular and Interventional Neurology, 2022)
Background The benefit of mechanical thrombectomy in patients with low Alberta Stroke Program Early Computed Tomography Score (ASPECTS) for short‐term outcomes is debatable and long‐term outcomes remain unknown. This retrospective, monocentric cohort study aimed to assess the association between reperfusion grade and the long‐term functional outcome measured with modified Rankin scale as well as the long‐term health‐related quality of life recorded at the last follow‐up in patients according to baseline ASPECTS (0–5 versus 6–10). Methods Deceased patients were identified from the Swiss population register and follow‐up telephone interviews were conducted with all surviving patients with stroke treated with mechanical thrombectomy between January 1, 2010, and December 31, 2018. Favorable outcome was defined as modified Rankin scale 0 to 3; health‐related quality of life was assessed using the 3‐level version of the EuroQol 5‐dimensional questionnaire. The EuroQol 5‐dimension utility index was calculated for statistical analyses. The reperfusion grade was core laboratory adjudicated using the expanded treatment in cerebral ischemia score. Adjusted odds ratios for the association between the reperfusion grade assessed by expanded treatment in cerebral ischemia and outcomes were calculated from multivariable logistic regression. Results Of the 1114 patients with available long‐term follow‐up records (median follow‐up, 3.67 years), 997 were included in the final analysis. Respectively, patients with low ASPECTS more often had complaints regarding mobility (67.1% versus 42.1%, P<0.001), self‐care (53.4% versus 31.2%, P<0.001), and usual activities (65.8% versus 41.4%, P<0.001) than patients with high ASPECTS, whereas reported pain/discomfort (65.7% versus 69.9%, P=0.49) and anxiety/depression (71.2% versus 78.9%, P=0.17) did not differ. In patients with low ASPECTS, increasing reperfusion grade was associated with a higher likelihood of long‐term favorable functional outcome (adjusted odds ratio, 1.43; 95% CI, 1.09–1.88 [P=0.01]) and health‐related quality of life (adjusted linear correlation coefficient, 0.05; 95% CI, 0.02–0.08) despite early extensive infarction. Conclusion Despite low baseline ASPECTS, a higher reperfusion grade results in better functional outcomes and may improve health‐related quality of life in the long term.